2015
DOI: 10.1099/jmm.0.000147
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of minocycline alone or in combination in multidrug-resistant Acinetobacter baumannii isolates

Abstract: Minocycline (MIN) usually shows good activity against Acinetobacter baumannii strains. The reintroduction to the market of intravenous MIN provides an additional agent to the limited options for the treatment of A. baumannii infections. The activity of MIN as a single agent and in combination with rifampicin (RIF), colistin (COL) or imipenem (IMI) was evaluated by means of killing curves and 24 h-time-kill curves in five A. baumannii isolates which were selected on the basis of different antimicrobial resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…The TetB efflux pump is the main determinants of minocycline resistance (Vilacoba et al, 2013). Minocycline therapy combined with colistin is effective for treating minocycline-resistant A. baumannii infections (Yang et al, 2016), and minocycline therapy combined with rifampicin, colistin, or imipenem has a synergistic effect in most of isolates without the tetB gene, but combined therapies are not synergistic in isolates with the tetB gene (Rodriguez et al, 2015). …”
Section: Prospective Treatment Optionsmentioning
confidence: 99%
“…The TetB efflux pump is the main determinants of minocycline resistance (Vilacoba et al, 2013). Minocycline therapy combined with colistin is effective for treating minocycline-resistant A. baumannii infections (Yang et al, 2016), and minocycline therapy combined with rifampicin, colistin, or imipenem has a synergistic effect in most of isolates without the tetB gene, but combined therapies are not synergistic in isolates with the tetB gene (Rodriguez et al, 2015). …”
Section: Prospective Treatment Optionsmentioning
confidence: 99%
“…Whether the administration of combinations occurred in more severe underlying infections or sicker patients and therefore resulted in lower success rates, or indeed, whether minocycline is more effective as a monotherapy, cannot be answered from this data. Many microbiological studies have reported the synergistic effects of minocycline when combined with other agents like rifampicin, imipenem, cefoperazone/sulbactam or colistin in in vitro experiments [42,43,44,45]. Similarly, in animal studies, combination regimens with rifampicin, amikacin or polymyxin B have also demonstrated promising results against experimental A. baumannii infections [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have evaluated polymyxin (polymyxin B or colistin) in combination with minocycline against A. baumannii in both in vitro and in vivo models of infection with favorable results (17)(18)(19). Bowers et al (20) determined that subinhibitory concentrations of polymyxin B (0.5 mg/liter) could increase intracellular minocycline concentrations (2 and 8 mg/liter) and enhance minocycline's activity in static time-kill experiments against three clinical isolates and one laboratory isolate (20) with polymyxin B MICs of Ն2 mg/liter and minocycline MICs ranging between 0.25 and 16 mg/liter.…”
Section: Discussionmentioning
confidence: 99%
“…Minocycline inhibits bacterial protein synthesis and has favorable tissue penetrability due to its lipophilicity (16). Minocycline combined with colistin is synergistic against multidrugresistant (MDR) A. baumannii (17)(18)(19) based on the hypothesis that polymyxin disrupts outer membrane integrity to raise intracellular concentrations of minocycline in Gramnegative bacteria (20,21). The objective of this study was to evaluate the rate and extent of killing activity of polymyxin B and minocycline alone and in combination against KPC-2-producing K. pneumoniae isolates using static in vitro time-kill studies.…”
mentioning
confidence: 99%